2011
DOI: 10.1097/sla.0b013e318212bff6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of D1 Versus D2 Gastrectomy for Gastric Adenocarcinoma

Abstract: On the basis of this meta-analysis we conclude that D1 gastrectomy is associated with significant fewer anastomotic leaks, postoperative complication rate, reoperation rate, decreased length of hospital stay and 30-day mortality rate. Finally, the 5-year survival in D1 gastrectomy patients was similar to the D2 cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…Previous reviews and meta-analyses have tried to clarify the debate [19][20][21][22][23][24]. With the publications of the short-term outcomes of the most recent trial (IGCSG-R01) and the 15-year follow-up of the Dutch trial [8], both of which reveal favorable results for the D2 resection, we sought to perform an updated meta-analysis of all RCTs comparing D1 and D2 procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews and meta-analyses have tried to clarify the debate [19][20][21][22][23][24]. With the publications of the short-term outcomes of the most recent trial (IGCSG-R01) and the 15-year follow-up of the Dutch trial [8], both of which reveal favorable results for the D2 resection, we sought to perform an updated meta-analysis of all RCTs comparing D1 and D2 procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis differs from those previously published as it includes the completed short-term results of the IGCSG-R01 trial. The recently published meta-analysis by Memon et al [23] only considered the interim analysis of the IGCSG-R01 trial [25]. Additionally, our meta-analysis does not include the D1 versus D3 trial reported by Robertson et al [26], which describes dissection around the celiac axis and para-aortic nodes as well as complete removal of the spleen and distal pancreas for D3 patients.…”
Section: Short-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some patients lose the opportunity of curative resection resulting from the aggressive nature of GC. Although chemoradiotherapy and targeted therapy have confirmed an improvement in host response rates, the cancer recurrences and metastases are frequently observed 2, 3, 4, 5, 6. The bacteria Helicobacter pylori ( H. pylori) is one of the major risk factors for GC development.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphadenectomy is considered essential for gastric cancer surgery; however, the extent of lymph node removal is still debated in the literature [1][2][3][4][5][6]. In Asia, extended lymph node dissection has long been the standard of care for patients with advanced gastric cancer [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%